Use of a combined oxygen and carbon dioxide transcutaneous electrode in the estimation of gas exchange during exercise. Issue 6 (June 1993) - Sridhar, M K; Carter, R; Moran, F; Banham, S W
Abstract : BACKGROUND–Accurate and reliable measurement of gas exchange during exercise has traditionally involved arterial cannulation. Non-invasive devices to estimate arterial oxygen (O2) and carbon dioxide (CO2) tensions are now available. A method has been devised and evaluated for measuring gas exchange during exercise with a combined transcutaneous O2 and CO2 electrode. METHODS–Symptom limited exercise tests were carried out in 24 patients reporting effort intolerance and breathlessness. Exercise testing was performed by bicycle ergometry with a specifically designed protocol involving gradual two minute workload increments. Arterial O2 and CO2 tensions were measured at rest and during exercise by direct blood sampling from an indwelling arterial cannula and a combined transcutaneous electrode heated to 45 degrees C. The transcutaneous system was calibrated against values obtained by direct arterial sampling before each test. RESULTS–In all tests the trend of gas exchange measured by the transcutaneous system was true to the trend measured from direct arterial sampling. In the 140 measurements the mean difference between the O2 tensions estimated by direct sampling and the transcutaneous method was 0.08 kPa (0.62 mm Hg, limits of agreement 4.42 and -3.38 mm Hg). The mean difference between the methods for CO2 was 0.02 kPa (0.22 mm Hg, limits of agreement 2.20 and -1.70 mm Hg). There was no morbidity associated with the use of the transcutaneous electrode heated to 45 degrees C. CONCLUSIONS–A combined transcutaneous O2 and CO2 electrode heated to 45 degrees C can be used to provide a reliable estimate of gas exchange during gradual incremental exercise in adults.